Parenting styles and their impact on their personalities It is an analytical theoretical study - Muhammad, Dr. Bakhan Ahmed Muhammad (Sulaimani Journal for Humanities, 2026)
This research is an analytical theoretical study in Sulaimani, as education is one of the main issues in today's world and an effective tool for changing and developing children's personality, as well as a way to protect society's values and standards It is also a major requirement for child development, so paying attention to child rearing methods is an important issue in the social life of society, and child rearing is the most sensitive process of creating and raising children that requires high skills The most favorable mental environment and the most material and human capacity for the process is prepared, as well as taking into account the mental, physical and mental state in the process of raising children are the main conditions for the success of the process. In view of this fact, in light of the importance of the subject, we felt it necessary to conduct research on child rearing methods to show the most important methods and their impact on children's personalities The most important objectives of the study are to try to conduct a theoretical analysis of the methods of child education and also to try to present the most important areas, principles and steps of child education and present the effect of different methods of education on children's personalities One of the most important findings of the study is that the use of different methods of education affects children's personalities, because healthy education using different methods can provide additional value to children and help guide parents in fulfilling their educational duties, and this helps It gives children a sense of independence and self-confidence and has a direct impact on their personality
Keywords: Education; Child; Child Rearing; Influence; Personality